If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -1f = 5 Solving 18 + -1f = 5 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1f = 5 + -18 Combine like terms: 18 + -18 = 0 0 + -1f = 5 + -18 -1f = 5 + -18 Combine like terms: 5 + -18 = -13 -1f = -13 Divide each side by '-1'. f = 13 Simplifying f = 13
| 3-m/6=8 | | 3-(2-f)+1=2(1-f) | | 4x+10+2x=16 | | a-7=-36 | | -11=6+2x-7 | | 3(3x-7)+5=2(2x+12) | | 5y-6-3y+5=0 | | sin9pie/3 | | 81=9x+9 | | 4x-6x+x-4+5x= | | 2/9-31=16=7/9 | | x^2-15x-52=0 | | 9=a/3-4 | | -3b+10(b-4)=-110 | | 8(x+4)-6x=x-2 | | 1-7x-1=-21 | | 5m+10=5m-10 | | -23=-4x-x-8 | | 6.1x-3+x-1.3= | | 29=10n+9 | | 5-8(s+1)=-9s+4 | | 6y-1= | | 0.3x-17=1.1x-25 | | 4/5x-1/5=9 | | 2(x+5)=36 | | 3x(x-2)+(x-2)= | | 3a+5+4a-6=2 | | x^2-10+11=0 | | -5-1.2= | | 2*log*x=log*2+log(3*x-4) | | 10+x-7x=-38 | | 8x+6(1+5x)=2 |